Religious Humanistic Learning in Improving Islamic Religious Education Learning Outcomes at Pesat Senior High School Bogor (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study analyzes the implementation of religious humanistic learning in Islamic Religious Education at Pesat Senior High School Bogor as a response to emerging dehumanization issues in Indonesian education, aiming to explain the concept, identify applied strategies, and evaluate the implications for students’ holistic development. Method: Using a qualitative case study approach through in-depth interviews, classroom observations, and documentation analysis, the data were triangulated to enhance validity and capture the real dynamics of religious humanistic learning practices. Results: The findings show that religious humanistic learning strengthens cognitive, affective, and psychomotor outcomes, with improved academic performance, evidenced by an average Islamic Religious Education score of 94. Teachers implement empathetic dialogue, contextual instruction, and value internalization to cultivate critical thinking, spirituality, and ethical behavior, while the school integrates religious habituation, digital ethics guidance, birrul walidain programs, and scholarship initiatives to support these goals. Twenty-first-century skills are enhanced through project-based learning, the Pesat Research Community, edufairs, and talent classes, preparing students to face global challenges creatively, independently, and responsibly in the future. Novelty: This study presents a comprehensive model of religious humanistic learning that integrates spiritual formation, ethical digital culture, parental devotion programs, and research-based activities, offering new insights into the alignment of humanistic pedagogy with Islamic educational values in the Indonesian secondary school context.